Assessing the impact of Minnesota's return to community initiative for newly admitted nursing home residents. (6th February 2019) - Hass, Zachary; Woodhouse, Mark; Grabowski, David C.; Arling, Greg
Abstract : Objective: To evaluate Minnesota's Return to Community Initiative's (RTCI) impact on community discharges from nursing homes. Data Sources: Secondary data were from the Minimum Data Set and RTCI staff (April 2014 – December 2016). The sample consisted of 18 444 non‐Medicaid nursing home admissions in Minnesota remaining for at least 45 days, with high predicted probability of community discharge. Study Design: The RTCI facilitates community discharge for non‐Medicaid nursing home residents by assisting with discharge planning, transitioning to the community, and postdischarge follow‐up. A key evaluation question is how many of those transitions were directly attributable to the program. Return to Community Initiative was implemented statewide without a control group. Program impact was measured using regression discontinuity, a quasi‐experimental design approach that leverages the programs targeting model. Principal Findings: Return to Community Initiative increased community discharge rates by an estimated 11 percent ( P  < 0.05) for the targeted population. The program effect was robust to time and increased with level of facility participation in RTCI. Conclusions: The RTCI had a modest yet significant impact on the community discharge rates for its targeted population. Findings have been applied in strengthening the RTCI's targeting approach and transitioning process.